2002
DOI: 10.1590/s0103-90162002000400016
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and test of the cropgro-dry bean model for edaphoclimatic conditions in the savanas of Central Brazil

Abstract: Simulation models are important tools for the analysis of cultivated systems to estimate the performance of crops in different environments. The CROPGRO-model (DSSAT) was calibrated and validated using Carioca bean (Phaseolus vulgaris L.) to estimate yield and the development of the crop, sown in three row spacings (0.4, 0.5, and 0.6 m) and two fertilization rates (300 and 500 kg ha -1 of 4-30-16 N-P-K), in Santo Antônio de Goiás, GO, Brazil. To calibrate the model a combination of the genetic coefficients tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
2
1
1
Order By: Relevance
“…In addition, the RMSE was low (2.47%). These results are consistent with previous studies that showed that the model appeared to simulate the phenology of the bean cultivars adequately (FARIA et al, 1997;MEIRELES et al, 2002). …”
Section: Estimated Duration Of the Phenological Stages Of The Beansupporting
confidence: 93%
“…In addition, the RMSE was low (2.47%). These results are consistent with previous studies that showed that the model appeared to simulate the phenology of the bean cultivars adequately (FARIA et al, 1997;MEIRELES et al, 2002). …”
Section: Estimated Duration Of the Phenological Stages Of The Beansupporting
confidence: 93%
“…The flowering was estimated as 54 days after sowing (DAS), the onset of the first pod as 61 DAS and the physiological maturity as 96 DAS. Other studies had already proved the ability of this model in simulating the phenology of other cultivars of beans, corroborating our findings (MEIRELES et al, 2002;OLIVEIRA et al, 2012). (Figure 3).…”
Section: Model Calibrationsupporting
confidence: 91%
“…In another study, DALLACORT et al (2005) studied different planting dates of beans, and observed a maximum LAI of 3.34 m 2 m -2 during the best growing season. However, these results are lower than those observed by MEIRELES et al (2002), who found IAFs of up to 6.47 m 2 m -2 in simulations.…”
Section: Model Testingcontrasting
confidence: 83%
“…Using these values worldwide leads to overestimated yields in regions with more extensive management. Extensive management characterized by low fertilizer inputs leads generally to reduced canopy growth and lower LAI (Meireles et al , 2002). As the model presently contains no explicit nutrient cycles, we proxy these processes by adapting the LAI max value to the fertilizer use level for two dominant CFTs: temperate cereals and maize.…”
mentioning
confidence: 99%